(untitled) (Bulletin of Environmental Science and Sustainable Management (e-ISSN 2716-5353), 2022)
In the foreseeable future, bioremediation is by far the most cost-effective method for removing noxious chemical toxins and organic contaminants, especially at low concentrations when other methods like physical or chemical procedures wouldn’t be successful. For the objective of bioremediation, we have isolated a molybdenum-reducing bacteria from agricultural soil. The ideal pH and temperature ranges for the bacterium to reduce molybdate to molybdenum blue (Mo-blue) are 6.3 and 6.8, respectively. The best electron donor for molybdate reduction was glucose, which was followed in descending order by sucrose, lactose, l-rhamnose, d-mannose, raffinose, d-adonitol, maltose, d-mannitol, melibiose, cellobiose, glycerol, and d-sorbitol. Phosphate concentrations of 7.5 mM and molybdate concentrations of 15 – 20 mM are also necessary. The Mo-blue that was formed had an absorption spectrum that was comparable to that of earlier Mo-reducing bacteria and closely resembled that of reduced phosphomolybdate. At 2 ppm, copper (II), mercury (I), and silver I hindered molybdenum reduction by 80.2, 74.8, and 30.4%, respectively. The bacterium was tentatively identified as Enterobacter aerogenes strain Amr-18 after phenotypic and biochemical identifications. The bacterium could thrive on the amides, acrylamide, acetamide, and propionamide and could use acrylamide as an electron donor for molybdenum reduction. This bacterium has a highly valued trait that makes it useful for bioremediation: the capacity to detoxify a variety of toxicants.